Sex-Specific Metabolic Impairments in a Mouse Model of Disrupted Selenium Utilization - Kremer, Penny M.; Torres, Daniel J.; Hashimoto, Ann C.; Berry, Marla J. (Frontiers in Nutrition, 2021)
The essential micronutrient selenium (Se) provides antioxidant defense and supports numerous biological functions. Obtained through dietary intake, Se is incorporated into selenoproteins via the amino acid, selenocysteine (Sec). Mice with genetic deletion of the Se carrier, selenoprotein P (SELENOP), and the Se recycling enzyme selenocysteine lyase (SCLY), suffer from sexually dimorphic neurological deficits and require Se supplementation for viability. These impairments are more pronounced in males and are exacerbated by dietary Se restriction. We report here that, by 10 weeks of age, female Selenop/Scly double knockout (DKO) mice supplemented with 1 mg/ml sodium selenite in drinking water develop signs of hyper-adiposity not seen in male DKO mice. Unexpectedly, this metabolic phenotype can be reversed by removing Se from the drinking water at post-natal day 22, just prior to puberty. Restricting access to Se at this age prevents excess body weight gain and restriction from either post-natal day 22 or 37 reduces gonadal fat deposits. These results provide new insight into the sex-dependent relationship between Se and metabolic homeostasis.